Sistem Pendeteksi Kebakaran Pada Apron Passenger Bus (APB) Berbasis Mikrokontroler - Budi Sulistyo, Aris; Dwifa, Benny; Widiangga, Nengah; Eka Nugraha, Asep (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2021)
This research is about constructing a prototype of fire detection warning system on Apron Passenger Bus. The prototype can detect certain possibility of fire and give early warning to the driver. It works automatically based on three sensors used, which are smoke sensor, temperature sensor and flame sensor. The prototype is constructed using these three sensors and combined with Arduino microcontroller. This microcontroller has a role of transmitting information to the alarm system as a fire indicator. Method used in this research begins with simulation of a fire warning system and continued by implementation on hardware. The prototype works successfully on detecting fire both on software and hardware basis.